2011
DOI: 10.4103/0973-029x.80016
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal NK/T-cell lymphoma, nasal type (angiocentric T-cell lymphoma): A review about the terminology

Abstract: Extranodal NK/T-cell lymphoma, nasal type (ENKL) is a rare lymphoid neoplasm, which in the past has been grouped with a variety of granulomatous diseases. It is an aggressive non-Hodgkin’s type characterized clinically by aggressive, nonrelenting destruction of the midline structures of the palate and nasal fossa. Despite the malignant clinical course, histological diagnosis can be difficult because of extensive tissue necrosis and multiple biopsies that are often required and has an ominous prognosis, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…These tumours are found to be associated with Epstein Barr virus and the prodromal stage of the disease may have an indolent course that may last many years. 19,20,21 These tumours show positive immunostaining to CD3, CD56. 21,22 Olfactory neuroblastoma is a rare tumour.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These tumours are found to be associated with Epstein Barr virus and the prodromal stage of the disease may have an indolent course that may last many years. 19,20,21 These tumours show positive immunostaining to CD3, CD56. 21,22 Olfactory neuroblastoma is a rare tumour.…”
Section: Discussionmentioning
confidence: 97%
“…19,20,21 These tumours show positive immunostaining to CD3, CD56. 21,22 Olfactory neuroblastoma is a rare tumour. Tural et al found only nineteen cases in a 24-year retrospective analysis.…”
Section: Discussionmentioning
confidence: 97%
“…It is more prevalent in Asian populations and native Americans of Central and South America (1)(2)(3)4). ENKTL is typically seen in adults but can occur in children as well (1)(2)(3). Approximately 70% of ENKTL are reported to be of NK cell origin (5).…”
Section: Discussionmentioning
confidence: 99%
“…ENKTL, nasal type, is a rare lymphoid neoplasm, representing approximately 1.5% of all lymphomas in the United States a (1-3). It is more prevalent in Asian populations and native Americans of Central and South America (1)(2)(3)4). ENKTL is typically seen in adults but can occur in children as well (1)(2)(3).…”
Section: Discussionmentioning
confidence: 99%
“…Histology of sarcoidosis demonstrates non caseating granulomas. Midline granuloma is a lethal malignant condition characterized by angiocentric and angiodestructive growth patterns with extensive mucosal ulceration and lymphomatous infiltrate (14,15). Many times the diagnosis is delayed and it may lead to further involvement of the adjacent structures and cosmetic disfigurement but fortunately in our patient there was a superficial ulcerative and crusting lesion over the tip of her nose which probably prompted her parents to seek early consultation and so based on clinical suspicion followed by histopathological confirmation with demonstration of epitheloid granulomas, necrosis and other supportive features suggestive of tuberculosis the patient was started on antitubercular chemotherapy.…”
Section: Discussionmentioning
confidence: 99%